Kemampuan Menghambat dan Sifat Hambatan Analog Kurkumin Terhadap Aktivitas Enzim Siklooksigenase - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT Curcumin analogues are compounds that were synthesized based on curcumin structure modified with substitution of dimethyl group at the two aromatic rings and C-a ketone cyclisation. The curcumin analogues employed were PGV-0 (Pentagamavunon-O), PGV-1 (Pentagamavunon-1) and HGV-1 (Heksagamavunon-1) with the respective molecule structures of C2]H20O5/ C^H^Oj and C24H26O3 The aim of this study was to find out the effect and the types of inhibition of curcumin analogues on cyclooxigenase enzyme activity. The experiments were performed using human platelets obtained from fresh human blood as a source of cyclooxygenase. The inhibitory effect of cyclooxygenase was calculated as the percentage of inhibitions in the presence of 0,1,5,10,15,20 yM of PGV-0 and 0,1,5,10,15 uM of PGV-1 and HGV-1 in the final concentration. The concentration of the substrate was 3 M-M. The type of inhibition on cyclooxygenase was determined from the Lineweaver-Burk plots with a concentrations of 0,5,10,15 mM of PGV-0 and 0,5,10 uM of PGV-1 and HGV-1. The concentration of the substrate were 1,3,5,7,9 |xM. Apparent Ki constants were calculated using the equation for competitive inhibition. The results of this study showed that the three curcumin analogues have the inhibitory potentiality on cyclooxygenase enzyme activity in the order of potentiality respectively PGV-0 was smaller than PGV-1, and PGV-1 had about the same potency of HGV-1. The types of inhibition on cyclooxygenase activity for the three curcumin analogues were competitive.